2021
DOI: 10.1029/2020ja028429
|View full text |Cite
|
Sign up to set email alerts
|

F Region Electric Field Effects on the Intermediate Layer Dynamics During the Evening Prereversal Enhancement at Equatorial Region Over Brazil

Abstract: It is well known that the electric field that controls the ionospheric plasma drifts is generated by the dynamo process in the E and F regions. During the day, the zonal electric field is directed to the east and produces the upward vertical drift, however, before its reversal to the west in the evening, a significant and fairly sharp increase in the eastward electric field is observed. This intensification in the vertical drift that is known as prereversal enhancement of the zonal electric field (PRE) is caus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…These results show that in general, the ILs occurrence resulted to be independent of the magnetic disturbances, since the referred two periods of geomagnetic activity are totally different from each other. However, their development/dynamics over Brazilian sector can be affected by disturbed electric fields, as shown by the results here presented and others previous publications (dos Santos et al 2019 andSantos et al 2021). Although the impacts of the geomagnetic activity on different layers of the ionosphere have been extensively studied, there is a lack of information about what happens in the ionospheric valley region during such conditions, mainly over the low and equatorial latitudes.…”
Section: Data Setsupporting
confidence: 55%
See 2 more Smart Citations
“…These results show that in general, the ILs occurrence resulted to be independent of the magnetic disturbances, since the referred two periods of geomagnetic activity are totally different from each other. However, their development/dynamics over Brazilian sector can be affected by disturbed electric fields, as shown by the results here presented and others previous publications (dos Santos et al 2019 andSantos et al 2021). Although the impacts of the geomagnetic activity on different layers of the ionosphere have been extensively studied, there is a lack of information about what happens in the ionospheric valley region during such conditions, mainly over the low and equatorial latitudes.…”
Section: Data Setsupporting
confidence: 55%
“…However, the larger descending rate (> 10 km/h) observed over the equatorial region may reveal an additional influence of the gravity waves in IL's dynamics. Additionally, Santos et al (2021) reported interesting events in which the ILs presented an upward movement at the same time in which the F layer rises due to the evening prereversal enhancement of the zonal electric field. Such characteristic was observed in most of the cases during a period of high solar activity, between October and April months, however a single case also was observed in 2009.…”
Section: F-regionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in addition to the vertical drift of the F layer, this study also shows the unique phenomenon of the E s layer being uplifting and moving downward near the center path of the moon shadow (Xiamen) during the solar eclipse (Figures 2b-2c). Santos et al (2021) analyzed the dynamics of the intermediate layer according to the ionosonde data of 357 days in 2003 and 293 days in 2009. However, they reported that the upward movement of the E s layer is a rare phenomenon under both geomagnetic quiet and disturbance conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al. (2021) analyzed the dynamics of the intermediate layer according to the ionosonde data of 357 days in 2003 and 293 days in 2009. However, they reported that the upward movement of the E s layer is a rare phenomenon under both geomagnetic quiet and disturbance conditions.…”
Section: Discussionmentioning
confidence: 99%